?A STUDY OF PAKISTANI GYPSUM BY X-RAY POWDER DIFFRACTION (Biological Sciences - PJSIR, 1996)
The Patala Formation of Palaeocene age, exposed at the Gandhala Nala area, Eastern Salt Range, Punjab, Pakistan, displays perfect crystals of gypsum. These crystals have been analysed by X-ray diffraction, scanning electron microscopy and wet chemical method, X-ray diffraction data are in good agreement with the reported values of ASTM. The chemical analysis of the samples indicates that the composition of the crystals is also close to theoretical for the compound CaSO 4' 2Hp. Thus, the deposit provides a source of relatively high purity gypsum crystals and may be used' as standard (reference) sample in local industries.